-4(1+7m)+3m=-(2m+4)

Simple and best practice solution for -4(1+7m)+3m=-(2m+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(1+7m)+3m=-(2m+4) equation:



-4(1+7m)+3m=-(2m+4)
We move all terms to the left:
-4(1+7m)+3m-(-(2m+4))=0
We add all the numbers together, and all the variables
-4(7m+1)+3m-(-(2m+4))=0
We add all the numbers together, and all the variables
3m-4(7m+1)-(-(2m+4))=0
We multiply parentheses
3m-28m-(-(2m+4))-4=0
We calculate terms in parentheses: -(-(2m+4)), so:
-(2m+4)
We get rid of parentheses
-2m-4
Back to the equation:
-(-2m-4)
We add all the numbers together, and all the variables
-25m-(-2m-4)-4=0
We get rid of parentheses
-25m+2m+4-4=0
We add all the numbers together, and all the variables
-23m=0
m=0/-23
m=0

See similar equations:

| 15+-11t-2t=16 | | 15x+6=12x+18 | | 2p+14=1.50p+20 | | 2.4x=1.2x+12 | | -6x-6x=-24 | | 3y-9=15y | | 12x+1=35 | | 2(k=2.5)=4k+3 | | 4(m+1)+4=20 | | –8p−12=5p+5−4 | | 12x=2(x+4) | | -20+100=8w+8w | | -13k+19k+–13=11 | | (3u-6)=18 | | 10r-8=-38 | | 77+n=n | | −16-4u=-16 | | 13k+19k+–13=11 | | -2(2q+1)+2q=-3 | | 14p+12=64 | | 6k-10=-3(3-2k)-1 | | -13-12r=-10r+15 | | -4(-3x+8)=-13 | | -124=-4(3-4n) | | 7/9+b=11/9 | | 20x-2=25x=12x+30 | | 6+10m=11 | | 2x+13=3(x-4) | | 6h+24=h-6 | | 10x=2=3x+33 | | 8(-5x-4)=7 | | 2x+12-8x=-6 |

Equations solver categories